Combined cytotoxic activity of an infectious, but non‐replicative herpes simplex virus type 1 and plasmacytoid dendritic cells against tumour cells. Issue 2 (15th September 2015) - Thomann, Sabrina; Boscheinen, Jan B.; Vogel, Karin; Knipe, David M.; DeLuca, Neal; Gross, Stefanie; Schuler‐Thurner, Beatrice; Schuster, Philipp; Schmidt, Barbara
Summary: Malignant melanoma is an aggressive tumour of the skin with increasing incidence, frequent metastasis and poor prognosis. At the same time, it is an immunogenic type of cancer with spontaneous regressions. Most recently, the tumoricidal effect of plasmacytoid dendritic cells (pDC) and their capacity to overcome the immunosuppressive tumour microenvironment are being investigated. In this respect, we studied the effect of the infectious, but replication‐deficient, herpes simplex virus 1 (HSV‐1) d 106S vaccine strain, which lacks essential immediate early genes, in pDC co‐cultures with 11 melanoma cell lines. We observed a strong cytotoxic activity, inducing apoptotic and necrotic cell death in most melanoma cell lines. The cytotoxic activity of HSV‐1 d 106S plus pDC was comparable to the levels of cytotoxicity induced by natural killer cells, but required only a fraction of cells with effector : target ratios of 1 : 20 ( P  < 0·05). The suppressive activity of cell‐free supernatants derived from virus‐stimulated pDC was significantly neutralized using antibodies against the interferon‐ α receptor ( P  < 0·05). In addition to type I interferons, TRAIL and granzyme B contributed to the inhibitory effect of HSV‐1 d 106S plus pDC to a minor extent. UV‐irradiated viral stocks were significantly less active than infectious particles, both in the absence and presence of pDC ( P  < 0·05), indicating that residual activity of HSV‐1 d 106S is a major component and sensitizes the tumour cells to interferon‐producing pDC. Three leukaemic cell lines were also susceptible to this treatment, suggesting a general anti‐tumour effect. In conclusion, the potential of HSV‐1 d 106S for therapeutic vaccination should be further evaluated in patients suffering from different malignancies.